Kajian Literatur : Faktor-Faktor Determinan Kesehatan Mental Remaja di Indonesia - Yolanda Anastasia Sihombing; Elfrida Nainggolan (Pusat riset dan Inovasi Nasional, 2025)
This systematic literature review aims to identify the key psychosocial and environmental determinants influencing adolescent mental health. Utilizing the PRISMA methodology, ten peer-reviewed articles published between 2019 and 2024 were analyzed. Key factors identified include parenting style, peer relationships, academic stress, bullying, digital media exposure, and the impact of the COVID-19 pandemic. The findings highlight the complexity of adolescent mental well-being and emphasize the necessity of integrated interventions involving families, schools, and communities to foster resilience.